PARADOKS FATWA DEWAN SYARIAH MAJELIS ULAMA INDONESIA DALAM REGULASI HUKUM PERBANKAN SYARIAH - Baehaqi, Ja'far (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2017)
This study intends to find the answer to the problem of judicial accommodation of the National Sharia Council of the Indonesian Ulama Council’s (NSC-IUC) fatwa in Islamic banking regulations. With the legislations approach the answers obtained that institutional structure of NSC-IUC and motivation discharge of fatwa of NSC-IUC making it well accepted as the basis of Islamic bank operations. But the framework of regulation could potentially cause uncertainty. Therefore it is necessary to strengthen the fatwa of NSC-IUC through three scenarios, namely the mandate, making the NSC-IUC as state institution, and the adoption and transformation of NSC-IUC’s fatwa into legislation better.[]Penelitian ini bermaksud mencari jawab terhadap problem yuridis akomodasi fatwa DSN-MUI dalam regulasi perbankan syari’ah. Dengan pendekatan perundang-undangan, diperoleh jawaban bahwa struktur kelembagaan DSN-MUI dan motivasi keluarnya fatwa DSN-MUI menjadikannya diterima secara baik sebagai dasar operasional bank syari’ah. Hanya saja kerangka pengaturannya berpotensi menimbulkan ketidakpastian. Oleh karena itu, diperlukan penguatan fatwa DSN-MUI melalui tiga skenario, yaitu pemberian mandat, menjadikan DSN-MUI sebagai institusi negara, adopsi dan transformasi fatwa DSN-MUI ke dalam peraturan perundang-undangan secara lebih baik.